2008
DOI: 10.1007/s11664-008-0385-8
|View full text |Cite
|
Sign up to set email alerts
|

Optical Hall Effect in Hexagonal InN

Abstract: Measurements of the optical Hall effect in naturally doped high-quality wurtzite-structure InN thin films by generalized ellipsometry reveal that both the surface and the interior (bulk) free electron densities decrease with powerlaw dependencies on the film thickness. We discover a significant deviation between the bulk electron and dislocation densities. This difference is attributed here to the existence of surface defects with activation mechanism different from bulk dislocations and identifies the possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
34
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 34 publications
9
34
0
Order By: Relevance
“…17 Our result for the sample of relatively high Al-content investigated here supports the theoretical predictions and is also in agreement with reports of vanishing effective mass anisotropy for similar electron concentrations in InN and GaN. 11 Slightly different mobility parameters of l ? ¼ ð3961Þ cm 2 /Vs and l k ¼ ð3261Þ cm 2 /Vs are determined for the directions perpendicular and parallel to the c-axis, respectively.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…17 Our result for the sample of relatively high Al-content investigated here supports the theoretical predictions and is also in agreement with reports of vanishing effective mass anisotropy for similar electron concentrations in InN and GaN. 11 Slightly different mobility parameters of l ? ¼ ð3961Þ cm 2 /Vs and l k ¼ ð3261Þ cm 2 /Vs are determined for the directions perpendicular and parallel to the c-axis, respectively.…”
supporting
confidence: 90%
“…1,5,8 Prerequisite for OHE application is the existence of sufficiently high ($10 17 :::10 18 cm À3 ) free charge carrier concentration. Previous investigations on GaAs, 1,9 AlGaInP and BInGaAs alloys, 8 AlInP, 5 ZnMnSe, 4,10 InN, 4,6,11 AlGaN/GaN high-electron mobility structures, 7,12 and graphene 13 showed that the OHE provides accurate values of the effective mass parameter that corroborate the results found, for example, from Shubnikov-de Haas measurements. Achieving reliable n-type conductivity in high-Al-content AlGaN and AlN is very challenging due to the high ionization energy of the common donors (O and Si).…”
supporting
confidence: 80%
“…The dependence of the electron effective mass on carrier concentration reported in Ref. 49 was used for the InN n-type films, while in the case of free holes a constant hole effective mass of 0.42 m 0 in InN 25 was assumed. A value of the electron effective mass in GaN of 0.22 m 0 was taken.…”
Section: Resultsmentioning
confidence: 99%
“…We note, however, that IRSE data on non-c-plane oriented samples and/or InN grown directly on sapphire as well as SE measurements in magnetic fields (OHE) provide enough sensitivity to determine the surface charge sheet density. 18,19,43 For the GaN template layer an electron concentration of 2:9 Â 10 17 cm À3 and a mobility of 102 cm 2 =Vs was obtained under assumption of an effective mass of 0:23 m 0 for GaN. 38 Using the dependence of the electron effective mass in InN on the carrier concentration as determined by OHE, 43 a buffer layer electron concentration of 1:1 Â 10 19 cm À3 and a mobility of 132 cm 2 =Vs were determined.…”
Section: Resultsmentioning
confidence: 99%
“…24,39 Further, parameters of free-charge carriers in different layers of a heterostructure can be determined individually. 24,43,44 Figure 3 shows the experimental and best-match model calculated data of OHE measurements performed on the undoped reference sample in the FIR spectral range at an angle of incidence of 72 . The differences of spectra taken at magnetic field strengths of þ1.5 T and À1.5 T for the off-diagonal Mueller-matrix elements MM 31 and MM 32 are shown.…”
Section: Resultsmentioning
confidence: 99%